Sifat antioksidatif ekstrak buah duwet (Syzygium cumin antioxidative properties of java plum (Syzygium cumini) fruit extract - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT A research on Java plum (Syzygium cumini) fruit as source of natural antioxidant has been done with special emphasis on the role of anthocyanins. The aims of this research were : to determine the extraction condition which include types of solvents, length of time, and temperature of extractions. The solvents combination consisted of : methanol-HC1 1%